Single-core double-shell high-entropy alloy reinforced titanium-based composite material and preparation method thereof
By depositing Ti thin layer on the surface of high-entropy alloy reinforced particles and forming core-shell heterostructure, the problem of insufficient interface bonding force between high-entropy alloy reinforced particles and titanium matrix is solved, and the mechanical properties and overall strong plasticity of the composite material are significantly improved.
Patent Information
- Application Number
- CN202510004225.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
The interface binding force between existing high-entropy alloy reinforced particles and titanium matrix is insufficient, resulting in incomplete or excessive interface reactions, resulting in brittle intermetallic compounds, affecting the overall performance of the composite material.
A single-core and double-shell high-entropy alloy-enhanced titanium-based composite material design is designed. By depositing a thin Ti layer on the surface of the high-entropy alloy-enhanced particles, and using low-temperature friction stir solid-phase additive technology, a core-shell heterostructure is formed, which significantly improves the interface bonding strength.
It significantly improves the mechanical properties of the composite material, reduces the stress concentration and interface defects caused by lattice mismatch, and enhances the overall strong plasticity of the material.
Smart Images

Figure CN119794341A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium-based composite material preparation, and specifically relates to a single-core double-shell high-entropy alloy reinforced titanium-based composite material and a preparation method thereof. Background Art
[0002] With the rapid development of my country's aviation and aerospace industry, the demand for structural materials has increasingly focused on characteristics such as light weight, high strength, high toughness and high stiffness. The preparation of titanium alloys and their composite materials, especially particle-reinforced titanium-based composite materials with high strength, high toughness and high elastic modulus, has become one of the key directions of national new material research and development.
[0003] Traditionally, reinforced particles are usually made of materials with high strength, high melting point and high hardness, such as ceramic particles. However, due to the large difference in thermal expansion coefficient between ceramic particles and titanium matrix, microcracks are easily formed at the interface, weakening the strengthening effect of the reinforced particles. In recent years, high entropy alloys have shown broad application prospects in the field of reinforced particles due to their excellent mechanical properties and good high temperature resistance. Existing studies have shown that the interfacial bonding between high entropy alloy reinforced particles and metal matrix still faces the problem of incomplete or excessive interfacial reaction, resulting in the generation of brittle intermetallic compounds, resulting in insufficient interface strength, which in turn affects the overall performance of the composite material. Common preparation methods for particle-reinforced titanium-based composites include powder metallurgy and additive manufacturing. Powder metallurgy usually requires post-processing such as extrusion and rolling to improve performance. Although additive manufacturing provides design freedom, the application and promotion of particle-reinforced titanium-based composites are limited due to organizational defects during melting and solidification.
[0004] To address the above challenges, the present invention adopts a core-shell heterostructure design by forming a coating layer ("shell") on the surface of the reinforced particles to improve the physical and chemical compatibility between the particles and the matrix, significantly improve the interfacial bonding strength, and effectively hinder the initiation and propagation of cracks, thereby significantly improving the mechanical properties of the composite material. Summary of the invention
[0005] In order to overcome the above problems, the present invention proposes a single-core double-shell high-entropy alloy reinforced titanium-based composite material and a preparation method thereof, by depositing a Ti thin layer on the surface of high-entropy alloy reinforced particles and adopting low-temperature stir friction solid phase additive technology, the single high-entropy alloy reinforced particles are transformed into core-shell heterostructure reinforced particles with a single-core double-shell structure, forming a coherent or semi-coherent interface, thereby significantly improving the mechanical properties of the material.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a single-core double-shell high-entropy alloy reinforced titanium-based composite material, comprising an inner core and a first shell and a second shell sequentially wrapped around the outer core, wherein the inner core is a high-entropy alloy reinforced particle with an FCC crystal structure, the first shell is a high-entropy alloy solid solution with a BCC crystal structure composed of a high-entropy alloy element and a titanium element, and the second shell is a β-Ti with a BCC crystal structure formed by diffusing the high-entropy alloy element into a titanium matrix;
[0008] The first shell layer and the second shell layer are both products of the interface reaction between the titanium matrix and the high entropy alloy reinforced particles.
[0009] A further improvement of the present invention is that the first shell layer is a circle of fine grains with a size of 0.5-1 μm wrapped around the outer core; the second shell layer is a circle of grains with a size of 2-6 μm wrapped around the first shell layer.
[0010] A further improvement of the present invention is that the high entropy alloy reinforced particles have an FCC crystal structure at room temperature, specifically Al x CoCrFeNi, x is in the range of 0.2≤x≤0.8, CoCrFeNi, CoCrFeMnNi or FeCoNiCuAl, and the volume fraction of the high entropy alloy reinforcement particles is 5%-20%;
[0011] The titanium matrix has an α phase at room temperature, specifically one of TA1, TA2, TA3 industrial pure titanium or one of TA7, Ti-8Al-1Mo-1V, Ti-3Al-2.5V titanium alloys, and the volume fraction of the titanium matrix is 80%-95%.
[0012] A further improvement of the present invention is that the particle size distribution range of the high entropy alloy reinforcement particles is 13 to 53 μm, the purity is ≥99%, and the shape is spherical.
[0013] In a second aspect, the present invention also provides a method for preparing a single-core double-shell high-entropy alloy reinforced titanium-based composite material, comprising the following steps:
[0014] Step 1, selecting high entropy alloy reinforcement particles and depositing a thin Ti layer on the surface of the high entropy alloy reinforcement particles by electroplating, forming a dense Ti coating by electrolytic reaction, and obtaining Ti-plated high entropy alloy reinforcement particles;
[0015] Step 2, selecting a titanium-based metal rod and preparing a plurality of hollow cylinders therein;
[0016] Step 3, filling the Ti-plated high entropy alloy reinforcement particles into the hollow cylinder, compacting it tightly, and obtaining a prepared metal rod;
[0017] Step 4: The prepared metal rod is used as additive feed and loaded into the fixture of a stir friction deposition additive equipment for stir friction solid phase additive to obtain a high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure.
[0018] A further improvement of the present invention is that the metal rod is a rectangular parallelepiped with a square bottom, wherein the bottom side S is 10 to 40 mm and the radius R of the hollow cylinder inside is 1 to 5 mm.
[0019] A further improvement of the present invention is that the number n of the hollow cylinders, the base S of the cuboid and the radius R of the cylinder are determined by the following formula:
[0020]
[0021] In the formula, n is the number of hollow cylinders contained in the metal bar, S is the base of the cuboid, and R is the radius of the cylinder.
[0022] A further improvement of the present invention is that the electroplating solution is a TiCl4 solution or a Ti(OC4H9)4 solution.
[0023] A further improvement of the present invention is that the current density of the electroplating is 1 to 10 A / dm 2 , temperature is 25-50℃, pH is 1-3, and electroplating time is 10-40min.
[0024] A further improvement of the present invention is that the tool head rotation speed of the friction stir deposition additive equipment is 500-2000 r / min, the forward speed is 10-150 mm / min, the feeding speed is 0.5-3 mm / s, and the upsetting force is 50-300 kN.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention provides a single-core double-shell high-entropy alloy reinforced titanium-based composite material, which forms a coherent or semi-coherent interface by constructing an FCC crystal structure core, a first layer of a BCC crystal structure high-entropy alloy solid solution shell and a second layer of a BCC crystal structure β-Ti shell, thereby effectively reducing the stress concentration and interface defect problems caused by lattice mismatch; in addition, when an external force acts, the FCC crystal structure core with good plasticity can effectively absorb and disperse the externally applied stress, while the double-layer BCC crystal structure shell can inhibit the formation and expansion of the core crack to a certain extent through the hardening effect. The combination of the two significantly improves the overall strength and plasticity of the composite material.
[0027] The present invention also provides a method for preparing a single-core double-shell high-entropy alloy reinforced titanium-based composite material. By using an electroplating method on the basis of traditional high-entropy alloy reinforced particles, a thin layer of Ti is deposited on the surface thereof, which significantly improves the compatibility of the high-entropy alloy reinforced particles with the titanium matrix and promotes the formation of the subsequent single-core double-shell structure; at the same time, the additive preparation of the material can be achieved by using stir friction deposition additives. The method is applicable to the preparation of multi-scale, multi-specification and multi-component composite materials. By changing the rod diameter, multiple, multi-scale, multi-component reinforced particles can be added, and gradient addition can also be achieved to prepare multi-specification composite materials. At the same time, stir friction deposition additive manufacturing can achieve the densification, homogenization and refinement of the material, improve the mechanical properties of the matrix, promote the formation of the interface, and greatly improve the mechanical properties of the material. The preparation method of the present invention is applicable to materials that are difficult to plastically process, such as titanium alloys, and has high efficiency and environmental protection, and the process is simple and the cost is low, which is suitable for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings described herein are only for explanation purposes and are not intended to limit the scope of the present invention in any way. In addition, the shapes and proportional dimensions of the various components in the drawings are only schematic, used to help understand the present invention, and are not intended to specifically limit the shapes and proportional dimensions of the various components of the present invention.
[0029] Figure 1 The EBSD phase diagram of the Ti-modified high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure prepared in Example 1 of the present invention;
[0030] Figure 2 This is a SEM image of a Ti-modified high entropy alloy reinforced titanium-based composite material having a single-core double-shell structure prepared in Example 2 of the present invention;
[0031] Figure 3 This is a SEM image of a Ti-modified high entropy alloy reinforced titanium-based composite material having a single-core double-shell structure prepared in Example 3 of the present invention;
[0032] Figure 4 This is a SEM image of a Ti-modified high entropy alloy reinforced titanium-based composite material having a single-core double-shell structure prepared in Example 4 of the present invention;
[0033] Figure 5 This is a SEM image of a high entropy alloy reinforced titanium-based composite material that does not form a single-core double-shell structure prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but it should not be understood that the above subject matter of the present invention is limited to the following embodiments. Without departing from the above technical ideas of the present invention, various substitutions and changes are made according to common technical knowledge and customary means in the field, which should all be included in the protection scope of the present invention.
[0035] The present invention provides a single-core double-shell high-entropy alloy reinforced titanium-based composite material, comprising an inner core and a first shell and a second shell sequentially wrapped around the outer core, wherein the inner core is a high-entropy alloy reinforced particle with an FCC crystal structure; the first shell is a high-entropy alloy solid solution with a BCC crystal structure generated by an interface reaction, and specifically, the first shell is a circle of fine grains with a size of 0.5-1 μm wrapped around the outer core;
[0036] The second shell layer is β-Ti with a BCC crystal structure formed by the diffusion of part of the high entropy alloy elements into the titanium matrix. Specifically, the second shell layer is a circle of grains with a size of 2-6 μm wrapped in the first shell layer; the first shell layer and the second shell layer are both the interface reaction products of the titanium matrix and the high entropy alloy reinforced particles.
[0037] The high entropy alloy reinforced particles mainly have FCC crystal structure at room temperature, specifically Al x CoCrFeNi, x is in the range of 0.2≤x≤0.8, CoCrFeNi, CoCrFeMnNi or FeCoNiCuAl;
[0038] The titanium matrix mainly has an α phase at room temperature, specifically one of TA1, TA2, TA3 industrial pure titanium or one of TA7, Ti-8Al-1Mo-1V, Ti-3Al-2.5V titanium alloys.
[0039] As an optional solution, the volume fraction of the high entropy alloy reinforcement particles is 5%-20%, and the volume fraction of the titanium matrix is 80%-95%.
[0040] As an optional solution, the particle size distribution range of the high entropy alloy reinforced particles is 13 to 53 μm, the purity is ≥ 99%, and the shape is spherical.
[0041] The present invention also provides a method for preparing a single-core double-shell high-entropy alloy reinforced titanium-based composite material, comprising the following steps:
[0042] Step 1, select one of TA1, TA2, TA3 industrial pure titanium or one of TA7, Ti-8Al-1Mo-1V, Ti-3Al-2.5V titanium alloy metal rods, and prepare a plurality of hollow cylinders inside the metal rods, wherein the metal rods are rectangular parallelepipeds with square bottoms, the bottom side S is 10-40 mm, and the radius of the hollow cylinder inside is 1-5 mm;
[0043] Step 2, select Al x One of CoCrFeNi (0.2≤x≤0.8), CoCrFeNi, CoCrFeMnNi or FeCoNiCuAl high entropy alloy reinforcement particles, and depositing a thin Ti layer on the surface of the high entropy alloy reinforcement particles by electroplating, forming a dense Ti coating by electrolytic reaction, and obtaining Ti-plated high entropy alloy reinforcement particles;
[0044] Specifically, the electroplating solution is titanium tetrachloride (TiCl4) solution or tetrabutyl titanium (Ti(OC4H9)4) solution; the current density is 1 to 10A / dm 2 , temperature is 25-50°C, pH is 1-3, and electroplating time is 10-40min;
[0045] Step 3, filling the Ti-plated high entropy alloy reinforcement particles in step 2 into the hollow metal raw material rod in step 1, compacting it tightly, and obtaining a prepared metal rod;
[0046] Step 4, the metal rod prepared in step 3 is used as additive feed, loaded into the fixture of the stir friction deposition additive equipment, the tool head speed is set to 500-2000r / min, the forward speed is 10-150mm / min, the feeding speed is 0.5-3mm / s, the top forging force is 50-300KN, and then stir friction solid phase additive is performed to obtain a high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure.
[0047] It should be noted that the volume fraction of the added high entropy alloy reinforcement particles is determined according to the volume of the metal rod occupied by a number of hollow cylinders. In step 1, the number n of hollow cylinders contained in the metal rod, the bottom side S of the cuboid, and the radius R of the cylinder are determined by the following formula:
[0048]
[0049] Where n is the number of hollow cylinders contained in the metal bar, S is the base of the cuboid, and R is the radius of the cylinder;
[0050] In addition, it should be noted that whether the first shell forms a stable high-entropy alloy solid solution and whether its crystal structure is BCC is determined by the Ω, δ parameters and electronegativity VEC. The calculation formula is as follows:
[0051]
[0052] Where, T m is the melting temperature of the alloy element, ΔH mix is the mixing enthalpy of all atoms in the first outer shell, ΔS mix is the mixing entropy of all atoms in the first outer shell;
[0053]
[0054] In the formula, (T m ) i is the melting point of the ith component of the alloy;
[0055] in:
[0056]
[0057] In the formula, c i and C j are the atomic percentages of the i-th and j-th components, respectively, is the mixing enthalpy of the binary liquid alloy. In the calculation, the mixing enthalpy values based on the Miedema binary liquid alloy macro model are shown in Table 2;
[0058] in
[0059]
[0060] Where R is the gas constant;
[0061]
[0062] In the formula, is the average atomic radius, which is calculated as follows:
[0063]
[0064] In the formula, r i The atomic radius of the specified element The atomic radius of each element is shown in Table 1;
[0065]
[0066] In the formula, VEC is the valence electron, C i is the atomic percentage of the ith component, (VEC) i is the valence electron concentration of each individual element, and the specific values are shown in Table 1;
[0067] When Ω≥1.1 and δ≤6.6, a stable high-entropy alloy solid solution is formed;
[0068] When VEC≥8, it tends to form FCC solid solution; when 6.87<VEC<8, it tends to form FCC+BCC two-phase solid solution; when VEC≤6.87, it tends to form BCC solid solution;
[0069] Whether the interface layer forms a stable solid solution is determined by formulas (1)-(8), where the melting point, atomic radius, electronegativity and other values of each element are shown in Table 1, and the mixing enthalpy value based on the Miedema binary liquid alloy macro model is shown in Table 2;
[0070] Table 1 Values of melting point, atomic radius and electronegativity of each element
[0071]
[0072] Table 2 Mixing enthalpy values based on Miedema binary liquid alloy macromodel
[0073]
[0074] Example 1
[0075] This embodiment is to prepare a high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure with a volume fraction of 10%. The high entropy alloy reinforcement particles are Al 0.6 CoCrFeNi, the titanium matrix is pure titanium TA1.
[0076] The preparation method comprises the following steps:
[0077] Step 1: Al 0.6 The CoCrFeNi high entropy alloy reinforcement particles were immersed in deionized water and the surface contaminants were removed by ultrasonic cleaning. 10 ml of TiCl4 was slowly dripped into 100 ml of cooled deionized water while stirring continuously to disperse the heat. An appropriate amount of hydrochloric acid was added to adjust the pH value of the solution to 2. The prepared electroplating solution was placed in an electrolytic cell and Al 0.6 The CoCrFeNi high entropy alloy reinforcement particles were fixed on the nickel mesh and used as the cathode. The platinum sheet was selected as the anode. The current density was set to 2A / dm 2 The electroplating time is 30 minutes. After electroplating, it is immediately rinsed with deionized water to remove the electroplating solution residue, and then placed in a vacuum drying oven to dry to obtain Ti-plated Al 0.6 CoCrFeNi high entropy alloy reinforced particles;
[0078] Step 2: Prepare a rectangular pure titanium rod with multiple hollow cylinders inside, with a grade of TA1 and a length of 180 mm. In order to make the high entropy alloy evenly distributed, a CNC machine tool is used to process five hollow cylinders inside the rectangular pure titanium rod. The bottom side length S of the rectangular parallelepiped and the radius R of the cylinder are determined by formula (1). After the processing is completed, the Al 0.6 The CoCrFeNi high entropy alloy reinforcement particles are filled into the pure titanium rod containing the hollow cylinder and compacted tightly to obtain a prepared metal rod;
[0079] It is calculated from formula (1) that when the radius r of the cylinder is 2.4 mm and the length S of the bottom side of the cuboid is 30 mm, the volume fraction requirement of the high entropy alloy is met.
[0080] Step 3: The metal rod prepared in step 2 is used as additive feed and loaded into the fixture of the friction stir solid phase additive equipment. The tool head speed is set to 1000r / min, the forward speed is 20mm / min, the feed speed is 0.7mm / s, and the upset force is 50KN. Then, the friction stir solid phase additive is performed to obtain an Al2O3 with a single-core double-shell structure. 0.6 CoCrFeNi high entropy alloy reinforced titanium matrix composites.
[0081] The single-core double-shell Al 0.6 The atomic percentages of each element in the first shell and the second shell of the CoCrFeNi high entropy alloy reinforced titanium matrix composite are shown in Table 3.
[0082] Table 3 Atomic percentage of each element in the first and second shells
[0083]
[0084]
[0085] Substituting the data in Table 3 into formulas (2), (3), (4), (5), (6) and (7) to calculate the first shell layer of this embodiment, Ω=1.25≥1.1, δ=6.14≤6.6, which meets the requirements for forming a stable high entropy alloy solid solution; substituting into formula (8) to obtain VEC=6.71≤6.87, the results show that the first shell layer of this embodiment is a high entropy alloy solid solution layer with a BCC crystal structure generated by interface reaction.
[0086] The titanium-based composite material prepared in this embodiment was tested by uniaxial tensile test. The results showed that the titanium-based composite material had excellent mechanical properties, with a tensile strength of 1008 MPa and an elongation of 15.6%. The EBSD phase diagram of the single-core double-shell structure titanium-based composite material prepared in this embodiment is shown in FIG. Figure 1 shown. Figure 1Al showing the core is FCC structure 0.6 CoCrFeNi high entropy alloy reinforced particles; according to the above calculation results and Table 3, the first shell is a high entropy alloy solid solution layer with a BCC crystal structure composed of six elements such as Al, Co, Cr, Fe, Ni, and Ti, and the second layer is a phase-changed β-Ti with a BCC crystal structure.
[0087] Example 2
[0088] This embodiment is to prepare a high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure with a mass fraction of 5%, the high entropy alloy reinforcement particles are CoCrFeNi, and the titanium matrix is a titanium alloy Ti-8Al-1Mo-1V.
[0089] The preparation method comprises the following steps:
[0090] Step 1: immerse the CoCrFeNi high entropy alloy reinforced particles in deionized water, remove surface contaminants through an ultrasonic cleaner, slowly drip 10 ml of TiCl4 into 100 ml of cooled deionized water, stir continuously to disperse heat, and add an appropriate amount of hydrochloric acid to adjust the pH value of the solution to 2; place the prepared electroplating solution in an electrolytic cell, fix the CoCrFeNi high entropy alloy reinforced particles on a nickel mesh and use it as a cathode, select a platinum sheet as an anode, and set the current density to 2 A / dm 2 The electroplating time is 30 min. After electroplating, the particles are immediately rinsed with deionized water to remove the residue of the electroplating solution, and then dried in a vacuum drying oven to obtain Ti-plated CoCrFeNi high entropy alloy reinforced particles.
[0091] Step 2, prepare a rectangular titanium alloy rod containing multiple hollow cylinders inside, the grade is Ti-8Al-1Mo-1V, and the length is 180 mm. In order to make the high entropy alloy evenly distributed, use a CNC machine tool to process three hollow cylinders inside the rectangular titanium alloy rod. The bottom side length S of the rectangular parallelepiped and the radius R of the cylinder are determined by formula (1). After the processing is completed, the Ti-plated CoCrFeNi high entropy alloy reinforcement particles are filled into the titanium alloy rod containing the hollow cylinders and compacted tightly to obtain a prepared metal rod;
[0092] It is calculated from formula (1) that when the radius R of the cylinder is 2.2 mm and the length S of the bottom side of the cuboid is 30 mm, the requirement for the volume fraction of the high entropy alloy is met.
[0093] Step 3, the metal rod prepared in step 2 is used as additive feed and loaded into the fixture of the stir friction solid phase additive equipment, the tool head speed is set to 1100r / min, the forward speed is 25mm / min, the feeding speed is 0.7mm / s, the top forging force is 50KN, and then stir friction solid phase additive is performed to obtain a CoCrFeNi high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure.
[0094] The atomic percentages of the elements in the first shell and the second shell of the CoCrFeNi high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure prepared in this embodiment are shown in Table 4.
[0095] Table 4 Atomic percentage of each element in the first and second shells
[0096]
[0097] Substituting the data in Table 4 into formulas (2), (3), (4), (5), (6) and (7) to calculate the first shell layer of this embodiment, Ω=1.32≥1.1, δ=6.43≤6.6, which meets the requirements for forming a stable high entropy alloy solid solution; substituting into formula (8) to obtain VEC=6.71≤6.87, the results show that the first shell layer of this embodiment is a high entropy alloy solid solution layer with a BCC crystal structure generated by interface reaction.
[0098] The titanium-based composite material prepared in this embodiment was tested by uniaxial tensile test. The results showed that the titanium-based composite material had excellent mechanical properties, with a tensile strength of 995 MPa and an elongation of 15.6%. The SEM image of the single-core double-shell structure titanium-based composite material prepared in this embodiment is shown in FIG. Figure 2 shown. Figure 2 The inner core is a CoCrFeNi high entropy alloy reinforced particle with an FCC structure. According to the above calculation results and Table 4, the first outer shell is a high entropy alloy solid solution layer with a BCC crystal structure composed of five elements, namely Co, Cr, Fe, Ni, and Ti, and the second layer is a phase-transformed β-Ti with a BCC crystal structure.
[0099] Example 3
[0100] This embodiment is to prepare a high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure with a mass fraction of 15%. The high entropy alloy reinforcement particles are Al 0.8 CoCrFeNi, the titanium matrix is titanium alloy Ti-3Al-2.5V.
[0101] The preparation method comprises the following steps:
[0102] Step 1: Al 0.8The CoCrFeNi high entropy alloy reinforcement particles were immersed in deionized water and the surface contaminants were removed by ultrasonic cleaning. 10 ml of TiCl4 was slowly dripped into 100 ml of cooled deionized water while stirring continuously to disperse the heat. An appropriate amount of hydrochloric acid was added to adjust the pH value of the solution to 2. The prepared electroplating solution was placed in an electrolytic cell and Al 0.8 The CoCrFeNi high entropy alloy reinforcement particles were fixed on the nickel mesh and used as the cathode. The platinum sheet was selected as the anode. The current density range was set to 2A / dm 2 The electroplating time is 30 minutes. After electroplating, it is immediately rinsed with deionized water to remove the electroplating solution residue, and then placed in a vacuum drying oven to dry to obtain Ti-plated Al 0.8 CoCrFeNi high entropy alloy reinforced particles.
[0103] Step 2: Prepare a rectangular titanium alloy rod containing multiple hollow cylinders inside, with a grade of Ti-3Al-2.5V and a length of 180 mm. In order to make the high entropy alloy evenly distributed, a CNC machine tool is used to process five hollow cylinders inside the rectangular titanium alloy rod. The length of the bottom side of the rectangular parallelepiped is S, and the radius of the cylinder is determined by formula (1). After the processing is completed, the Al 0.8 The CoCrFeNi high entropy alloy reinforcement particles are filled into the titanium alloy rod containing the hollow cylinder and compacted tightly to obtain a prepared metal rod;
[0104] It is calculated from formula (1) that when the radius R of the cylinder is 3.9 mm and the length S of the bottom side of the cuboid is 40 mm, the requirement for the volume fraction of the high entropy alloy is met.
[0105] Step 3, the metal rod prepared in step 2 is used as additive feed and loaded into the fixture of the stir friction solid phase additive equipment, the tool head speed is set to 1100r / min, the forward speed is 20mm / min, the feeding speed is 0.7mm / s, the top forging force is 50KN, and then stir friction solid phase additive is performed to obtain a CoCrFeNi high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure.
[0106] The single-core double-shell Al 0.8 The VEC values and atomic percentages of the elements in the first and second shells of the CoCrFeNi high entropy alloy reinforced titanium-based composites are shown in Table 5.
[0107] Table 5 Atomic percentage of each element in the first and second shells
[0108]
[0109] Substituting the data in Table 5 into formulas (2), (3), (4), (5), (6) and (7) to calculate the first shell layer of this embodiment, Ω=1.28≥1.1, δ=6.31≤6.6, which meets the requirements for forming a stable high entropy alloy solid solution; substituting into formula (8) to obtain VEC=6.58≤6.87, the results show that the first shell layer of this embodiment is a high entropy alloy solid solution layer of a BCC crystal structure generated by interface reaction.
[0110] The titanium-based composite material prepared in this embodiment was tested by uniaxial tensile test. The results showed that the titanium-based composite material had excellent mechanical properties, with a tensile strength of 968 MPa and an elongation of 18.2%. The SEM image of the single-core double-shell structure titanium-based composite material prepared in this embodiment is shown in FIG. Figure 3 shown. Figure 3 Al showing the core is FCC structure 0.8 CoCrFeNi high entropy alloy reinforced particles; according to the above calculation results and Table 5, the first shell is a high entropy alloy solid solution layer with a BCC crystal structure composed of six elements such as Al, Co, Cr, Fe, Ni, and Ti, and the second layer is a phase-changed β-Ti with a BCC crystal structure.
[0111] Example 4
[0112] This embodiment is to prepare a high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure with a mass fraction of 20%, the high entropy alloy reinforcement particles are CoCrFeMnNi, and the titanium matrix is titanium alloy TA7.
[0113] The preparation method comprises the following steps:
[0114] Step 1: immerse the CoCrFeMnNi high entropy alloy reinforced particles in deionized water, remove surface contaminants through an ultrasonic cleaner, slowly drip 10ml of TiCl4 into 100ml of cooled deionized water, stir continuously to disperse heat, and add an appropriate amount of hydrochloric acid to adjust the pH value of the solution to 2; place the prepared electroplating solution in an electrolytic cell, fix the CoCrFeMnNi high entropy alloy reinforced particles on a nickel mesh and use it as a cathode, select a platinum sheet as an anode, and set the current density range to 2A / dm 2 The electroplating time is 30 min. After electroplating, the particles are immediately rinsed with deionized water to remove the residue of the electroplating solution and dried in a vacuum drying oven to obtain Ti-plated CoCrFeMnNi high entropy alloy reinforced particles.
[0115] Step 2, prepare a rectangular titanium alloy rod containing multiple hollow cylinders inside, with a grade of TA7 and a length of 180 mm. In order to make the high entropy alloy evenly distributed, use a CNC machine tool to process 5 hollow cylinders inside the rectangular titanium alloy rod. The bottom side length S of the rectangular parallelepiped and the radius R of the cylinder are determined by formula (1). After the processing is completed, the Ti-plated CoCrFeMnNi high entropy alloy reinforcement particles are filled into the titanium alloy rod containing the hollow cylinders and compacted tightly to obtain a prepared metal rod;
[0116] It is calculated from formula (1) that when the radius R of the cylinder is 4.5 mm and the length S of the bottom side of the cuboid is 40 mm, the volume fraction requirement of the high entropy alloy is met.
[0117] Step 3, the metal rod prepared in step 2 is used as additive feed and loaded into the fixture of the stir friction solid phase additive equipment using a continuous rod feeding mechanism, the tool head speed is set to 1100r / min, the forward speed is 20mm / min, the feeding speed is 0.7mm / s, and the upsetting force is 50KN, and then stir friction solid phase additive is performed to obtain a CoCrFeMnNi high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure.
[0118] The VEC values and atomic percentages of the elements in the first shell and the second shell of the CoCrFeMnNi high entropy alloy reinforced titanium-based composite material with a single core and double shell structure prepared in this embodiment are shown in Table 6.
[0119] Table 6 Atomic percentage of each element in the first and second shells
[0120]
[0121]
[0122] Substituting the data in Table 6 into formulas (2), (3), (4), (5), (6) and (7) to calculate the first shell layer of this embodiment, Ω=1.18≥1.1, δ=6.45≤6.6, which meets the requirements for forming a stable high entropy alloy solid solution; substituting into formula (8) to obtain VEC=6.68≤6.87, the results show that the first shell layer of this embodiment is a high entropy alloy solid solution layer with a BCC crystal structure generated by interface reaction.
[0123] The titanium-based composite material prepared in this embodiment was tested by uniaxial tensile test. The results showed that the titanium-based composite material had excellent mechanical properties, with a tensile strength of 1046 MPa and an elongation of 12.2%. The SEM image of the single-core double-shell structure titanium-based composite material prepared in this embodiment is shown in FIG. Figure 4 shown. Figure 4The inner core is a CoCrFeMnNi high entropy alloy reinforced particle with an FCC structure. According to the above calculation results and Table 6, the first outer shell is a high entropy alloy solid solution layer with a BCC crystal structure composed of six elements, namely Co, Cr, Fe, Mn, Ni, and Ti, and the second layer is a phase-changed β-Ti with a BCC crystal structure.
[0124] Comparative Example 1
[0125] This comparative example is to prepare a titanium-based composite material with a volume fraction of 20%, using pure titanium TA2 as a titanium matrix and FeCoNiCuAl as high entropy alloy reinforcement particles. The difference is that the high entropy alloy reinforcement particles are not plated with Ti, and the titanium-based composite material is directly prepared. The preparation method includes the following steps:
[0126] Step 1, prepare a rectangular pure titanium rod containing multiple hollow cylinders inside, with a grade of TA2 and a length of 180 mm. In order to make the high entropy alloy evenly distributed, use a CNC machine tool to process 5 hollow cylinders inside the rectangular pure titanium rod. The bottom side length S of the rectangular parallelepiped and the radius R of the cylinder are determined by formula (1). After the processing is completed, the FeCoNiCuAl high entropy alloy reinforcement particles are filled into the pure titanium rod containing the hollow cylinder and compacted tightly to obtain a prepared metal rod;
[0127] It is calculated from formula (1) that when the radius r of the cylinder is 4.5 mm and the length S of the bottom side of the cuboid is 40 mm, the volume fraction requirement of the high entropy alloy is met.
[0128] Step 2: Use the metal rod prepared in step 1 as additive feed and load it into the fixture of the stir friction solid phase additive equipment. Set the tool head speed to 1100r / min, the forward speed to 20mm / min, the feed speed to 0.7mm / s, and the upset force to 50KN. Then, stir friction solid phase additive is performed to obtain a single-core double-shell structured FeCoNiCuAl high entropy alloy reinforced titanium-based composite material.
[0129] The titanium-based composite material prepared in this comparative example was tested by uniaxial tensile test. The results showed that the mechanical properties of the titanium-based composite material were greatly reduced, the tensile strength was only 760Mpa, and the elongation was only 14.6%. This comparative example did not produce a single-core double-shell structure, but only a small number of shell layers, such as Figure 5 The interface between the high entropy alloy reinforced particles and the matrix prepared in this comparative example is clear, no obvious interface products are generated, and only the FeCoNiCuAl core structure exists.
[0130] Comparative Example 2
[0131] Chinese patent CN112030024A uses HDH titanium powder as the matrix and CaC2 / CaB6 powder as the reinforcement to prepare a titanium-based composite material using a powder metallurgy method, and its tensile strength is 820MPa and its elongation is 26%. Compared with titanium-based composite materials prepared by traditional powder metallurgy methods, the mechanical properties of the high-entropy alloy reinforced titanium-based composite materials with a single-core double-shell structure prepared by the method described in the present invention have been significantly improved.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A single-core double-shell high-entropy alloy reinforced titanium-based composite material, characterized in that: It comprises an inner core and a first outer shell and a second outer shell which are sequentially wrapped around the outer core, wherein the inner core is a high entropy alloy reinforced particle with an FCC crystal structure, the first outer shell is a high entropy alloy solid solution with a BCC crystal structure composed of a high entropy alloy element and a titanium element, and the second outer shell is β-Ti with a BCC crystal structure formed by diffusing the high entropy alloy element into a titanium matrix; The first shell layer and the second shell layer are both products of the interface reaction between the titanium matrix and the high entropy alloy reinforced particles.
2. The single-core double-shell high-entropy alloy reinforced titanium-based composite material according to claim 1, characterized in that: The first shell layer is a circle of fine grains with a size of 0.5-1 μm wrapped around the outer core; the second shell layer is a circle of grains with a size of 2-6 μm wrapped around the first shell layer.
3. The single-core double-shell high-entropy alloy reinforced titanium-based composite material according to claim 1, characterized in that: The high entropy alloy reinforcement particles have an FCC crystal structure at room temperature, specifically Al x CoCrFeNi, x is in the range of 0.2≤x≤0.8, CoCrFeNi, CoCrFeMnNi or FeCoNiCuAl, and the volume fraction of the high entropy alloy reinforcement particles is 5%-20%; The titanium matrix has an α phase at room temperature, specifically one of TA1, TA2, TA3 industrial pure titanium or one of TA7, Ti-8Al-1Mo-1V, Ti-3Al-2.5V titanium alloys, and the volume fraction of the titanium matrix is 80%-95%.
4. The single-core double-shell high-entropy alloy reinforced titanium-based composite material according to claim 1, characterized in that: The high entropy alloy reinforced particles have a particle size distribution range of 13 to 53 μm, a purity of ≥99%, and a spherical shape.
5. A method for preparing a single-core double-shell high-entropy alloy reinforced titanium-based composite material according to claims 1-4, characterized in that: The following steps are involved: Step 1, selecting high entropy alloy reinforcement particles and depositing a thin Ti layer on the surface of the high entropy alloy reinforcement particles by electroplating, forming a dense Ti coating by electrolytic reaction, and obtaining Ti-plated high entropy alloy reinforcement particles; Step 2, selecting a titanium-based metal rod and preparing a plurality of hollow cylinders inside the rod; Step 3, filling the Ti-plated high entropy alloy reinforcement particles into the hollow cylinder, compacting it tightly, and obtaining a prepared metal rod; Step 4: The prepared metal rod is used as additive feed and loaded into the fixture of a stir friction deposition additive equipment for stir friction solid phase additive to obtain a high entropy alloy reinforced titanium-based composite material with a single-core double-shell structure.
6. The method for preparing a single-core double-shell high-entropy alloy reinforced titanium-based composite material according to claim 5, characterized in that: The metal rod is a rectangular parallelepiped with a square bottom, wherein the bottom side S is 10-40 mm and the radius r of the hollow cylinder inside is 1-5 mm.
7. The method for preparing a single-core double-shell high-entropy alloy reinforced titanium-based composite material according to claim 6, characterized in that: The number n of the hollow cylinders, the base S of the cuboid and the radius R of the cylinder are determined by the following formula: Where n is the number of hollow cylinders contained in the metal rod, S is the base of the cuboid, and R is the radius of the cylinder.
8. The method for preparing a single-core double-shell high-entropy alloy reinforced titanium-based composite material according to claim 5, characterized in that: The electroplating solution is a TiCl4 solution or a Ti(OC4H9)4 solution.
9. The method for preparing a single-core double-shell high-entropy alloy reinforced titanium-based composite material according to claim 5, characterized in that: The current density of the electroplating is 1 to 10 A / dm 2 , temperature is 25-50℃, pH is 1-3, and electroplating time is 10-40min.
10. The method for preparing a single-core double-shell high-entropy alloy reinforced titanium-based composite material according to claim 5, characterized in that: The tool head rotation speed of the friction stir deposition additive equipment is 500-2000 r / min, the forward speed is 10-150 mm / min, the feeding speed is 0.5-3 mm / s, and the upsetting force is 50-300 kN.
Citation Information
Patent Citations
High-strength high-plasticity titanium-based composite material and preparation method thereof
CN112030024A